Dynamics Modeling and Inherent Vibration Characteristic Analysis of Multi-motor Parallel Drive-transmission System - Li Liu; Ruizhi Shu; Jin Huang; Rulong Tan; Benyuan Fu (Jixie chuandong)
In order to understand the inherent vibration characteristics of multi-motor parallel drive-transmission system， and reveal the influence of system stiffness parameters on its natural frequency， considering the nonlinear factors such as time-varying meshing stiffness and messing error， the coupling dynamics model of multi-motor parallel drive-transmission system is established by using lumped-mass method. According to the trait of the vibration displacement of center components， the three typical low-order vibration modes are given， that is， torsional vibration mode， transverse vibration model and planet vibration mode. Then， the influence of meshing stiffness and support stiffness on the natural frequencies is studied. The results show that the other frequency components are sensitive to the change of system stiffness parameters except high order frequencies， and the coupling effect of system should be taken into full account when solving the natural frequency of the system. Meanwhile， the mode jumping will occur when the system stiffness parameters change， namely， a sudden change in the vibration mode of system， and it increases the complexity of the dynamic behavior of the system. Therefore， in the process of dynamic design， the mode jumping point should be avoided as much as possible to prevent the multi-order resonance from occurring.